Morphological Sources and Evidences in Ibn Hisham’s Major Commentary on Ibn Malik’s Alfiyyah - العيبي زهراء جبار; صادق مريم جعفر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
In this research, I studied the morphological sources and evidence of Ibn Hisham Al-Ansari in his major commentary on Ibn Malik’s Alfiyyah. I followed descriptive and ،analytical approach, dividing the research into two sections, preceded by an introduction and followed by a conclusion that included the most important results. The first section was entitled Ibn Hisham’s Sources in the Commentary. I studied the scholars from whom he took, the books from which he took, and the languages from which he took. The second section: Ibn Hisham’s Evidence in the Commentary. I mentioned his evidence from the Holy Quran and the speech of the Arabs "poetry and pros". The aim of the research is to identify the morphological approach adopted by Ibn Hisham in his commentary. Keywords: Ibn Hisham, sources, evidence.